Analisa Kinerja Personel di XXX Firma Hukum dengan Metode Kuantitatif - Fatoni Fatoni; Mohamad Firdaus (Jurnal Ilmiah Multidisiplin Ilmu, 2025)
Human resource (HR) performance evaluation is a crucial aspect in the management of professional service organizations, including law firms. This study aims to analyze the performance of seven personnel at XXX Law Firm using a quantitative method. Data were obtained through performance indicator-based surveys and training participation records over the past year. The results show that personnel with higher training frequency, such as MF and JH, tend to have better performance scores. The analysis also reveals a positive relationship between training frequency and individual performance levels. This study recommends a more structured HR development program to improve overall performance.